Methodology of Assessing Risks to Sustainable supply Chain of an Insurance Company - Lyudmila Tsvetkova; Tatiana Yurieva; Darya Karpova; Leonid Khuzhamov (International Journal of Supply Chain Management, 2019)
Tough competition for one of the unique resources the companies strive for is a set of stable communications with their suppliers who act as stakeholders for the business in the supply chain management strategy. Thus, there is a link between the resource concept of competitiveness and the concept of stakeholder management. Such an approach makes it necessary to develop a distribution model between stakeholders of limited funds to pay for them, ensuring their satisfaction and stable participation in the exchange process. This requires clear definitions of financial flows in logistics and supply chain management. The paper presents a model for determining the significance of relations with the insurance company’s shareholders. The first hypothesis concerns the possibility to describe the relative importance of the resource supplied by each stakeholder, and its place in the ranked series. At the same time, the authors propose such a series both for a developing regional company and for a developed federal insurer. Such a series should correspond to the ranked series of growth rates of payment for each resource acquired from the corresponding stakeholder. The second hypothesis is that these series of relative position of indicators growth rates corresponding the significance series of a particular resource can serve as a standard for monitoring the insurer's stable relations with stakeholders. The degree of discrepancy between the actual indicators included in the series and the standard ones can be used as a measurement of the risk to insurance reserves sufficiency of an insurance company due to unreliable communications with stakeholders and problems in accessing required resources. Regular monitoring the accordance with the standard balance of the main indicators of insurance activities ensures guaranteed compliance with regulatory requirements, the fulfillment of insurance commitments to policyholders, profitability of investors' capital, and meeting their commitments to intermediaries, staff and management.